Allergy Prevention Mechanisms of Human Milk Proteomes in Infants: A Scoping Review - Abdul Ghani, Radiah; Shaharul, Nurul Faqihah; Eka Nurhayati; Tengku Azhar, Tengku Norbaya (International Journal of Allied Health Sciences, 2025)
Background: There has been an evident rise in global prevalence of allergic diseases, such as food allergies, eczema, asthma, and allergic rhinitis but most notably in infants in recent times. Human milk contains diverse bioactive compounds that modulate immunity and protect against allergies. Of the main bioactive components of human milk, the human milk proteome, a broad spectrum of proteins as well as peptides has emerged as a key agent in modifying allergic reactions.This study aims to explore the relationship between the human milk proteome and the development of allergies in infants, focusing on their mechanisms in preventing allergen sensitivity Methods: A comprehensive search of peer-reviewed articles published between 2015-2025 was conducted in PubMed, Scopus, and ScienceDirect using the keywords: (“human milk” OR “breast milk”) AND (“proteome” OR “proteins”) AND (“allergy” OR “hypersensitivity”) AND (“infant” OR “newborn”). Of 533 articles retrieved, 26 passed screening, and 4 met the inclusion criteria, as illustrated in the PRISMA-ScR flow diagram. Results: There are 7 proteomes of human milk found that contain immunological components, including immunoglobulins like IgG, secretory IgA (SIgA) and interleukin-10 (IL-10). These components are involved in different mechanisms that prevent sensitivity to allergens such as transferring passive immunity that blocks allergen sensitization and promote immune tolerance by modulating inflammatory responses. The types of allergies included in this study are food allergies, atopic dermatitis, allergic rhinitis, asthma, allergic sensitization, eczema and respiratory allergies such as pollen allergies. Conclusion: The study highlights the imperative role of human milk proteomes such as immunoglobulins, sIgA, and IL-10 in shaping the immune tolerance and preventing allergies in infants. Further studies will be needed to investigate the synergistic roles of these bioactive components and their sustained effects on allergy prevention to improve global public health.